Recognition of Carboxylate Anions and Carboxylic Acids by Selenium-Based New Chromogenic Fluorescent Sensor: A Remarkable Fluorescence Enhancement of Hindered Carboxylates - Goswami, Shyamaprosad; Hazra, Anita; Chakrabarty, Rinku; Fun, Hoong-Kun (Organic letters, 2009)
A selenium metal-based new fluorescence sensor 5-pivaloylamino-1,2,5-selenodiazolo[3,4-d]pyrimidin-7-(6H)-one (receptor 1) has been reported for the recognition of monocarboxylic acids and carboxylate anions both by UV−vis and fluorescence methods. Receptor 1 recognizes carboxylate anions more than monocarboxylic acids and it is a selective sensor for carboxylates with specially hindered carboxylate anions. The changes of fluorescence intensity are remarkably enhanced with red shift in presence of bulky carboxylate anions. The X-ray crystal structure of receptor 1 with pivalic acid has been reported.